2009
DOI: 10.1177/0032885509334755
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Level of Service Inventory—Revised and the Level of Service Inventory: Screening Version With a Sample of Probationers

Abstract: Level of risk is proving to be an important characteristic in effectively serving offender populations. A major limitation to the use of risk assessments is agency resources. There are several screening instruments available that could significantly decrease the amount of resources that are needed to assess for risk. This article assesses the effectiveness of the Level of Service Inventory: Screening Version on 483 probationers in a western state resulting in a 2% false-positive rate. Policy implications are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Numerous meta‐analytic studies have demonstrated the LSI‐R's efficacy at predicting recidivism in various intuitional and correctional settings (Gendreau, Goggin, and Smith, ; Lowenkamp, Lovins, and Latessa, ; Smith, Cullen, and Latessa, ). Similar to the PCRA, this tool consists of 43 items that reflect the following risk predictive characteristics: criminal history, education and employment, family and marital situation, leisure and recreation, companions, alcohol or drug problems, antisocial patterns, pro‐criminal attitudes, and barriers to release.…”
mentioning
confidence: 99%
“…Numerous meta‐analytic studies have demonstrated the LSI‐R's efficacy at predicting recidivism in various intuitional and correctional settings (Gendreau, Goggin, and Smith, ; Lowenkamp, Lovins, and Latessa, ; Smith, Cullen, and Latessa, ). Similar to the PCRA, this tool consists of 43 items that reflect the following risk predictive characteristics: criminal history, education and employment, family and marital situation, leisure and recreation, companions, alcohol or drug problems, antisocial patterns, pro‐criminal attitudes, and barriers to release.…”
mentioning
confidence: 99%
“…Again, it gains added credibility because it is rooted in the empirical literature on predictors of recidivism and is integrated with a prominent paradigm of correctional treatment-which are the key principles of effective intervention (Cullen, 2002; see also Cullen and Gendreau, 2000;Gendreau et al, 2006;Ogloff and Davis, 2004). Across North America, the LSI-R is in use in more than 900 correctional agencies (Lowenkamp, Lovins, and Latessa, 2009; see also Listwan, Johnson, Cullen, and Latessa, 2008).…”
mentioning
confidence: 99%
“…Developed in the mid-1980s, the LSI-R is frequently used at both sentencing and probation stages of the criminal justice system to "guide sentencing decisions, placement in correctional programs, institutional assignments, and release from institutional custody." 155 The LSI-R uses fifty-four factors in the "areas of Criminal History, Education and Employment, Financial, Family, Accommodations, Leisure and Recreation, Companions, Alcohol and Drugs, Emotional and Personal Issues, and Attitudes and Orientation." 156 These factors then generate a risk prediction of each offender's likelihood of recidivism.…”
Section: Equal Protection Under Algorithms 327mentioning
confidence: 99%